Autologous Fat Grafting: Whom does it satisfy: Patient or Surgeon? - Patil Bhushan Ramesh; Sankhe Manashree; Guruswamy Vishwanath (Journal of Marine Medical Society, 2025)
Introduction: Autologous fat grafting (AFG) is a versatile and minimally invasive technique in the hands of the plastic surgeon for the correction of contour and other volume deficits. The objective of this study was to assess the efficacy of correction of these defects using AFG in terms of improvement in appearance, as judged both by patient and clinician evaluation. Methods: This prospective study was conducted from 2012 to 2023. Thirty cases of contour and other defects underwent correction by AFG by a single surgeon using a single technique. The patients were evaluated by themselves and by an independent surgeon preoperatively and at 6 months postoperatively using a Likert scale. Data were evaluated using MS Excel, Python 3.9.18, and SPSS Statistics. Results: Thirty patients were studied as described. Significant improvement was found across age groups and indications. The improvement in scores was significant, both in the clinician and patients’ self-evaluations and was comparable. No significant complications were encountered. Conclusion: AFG appears to be a safe, minimally invasive, consistently reproducible tool for the correction of contour and other volume deficits.